Kenophytes in Ukrainian woods - Onyshchenko, Viktor (Hacquetia, 2019)
On the basis of the analysis of data on 2502 vegetation plots sampled in 1990-2016, distribution of alien vascular plants species in the woods of Ukraine is described. In Ukraine, as in other European countries, the highest proportion of kenophytes in species composition is in floodplain woods. The lowest their proportion is characteristic for bog woods and mountain woods. Most frequent species are Impatiens parviflora (predominantly in broad-leaved woods) and Conyza canadensis (pine woods on sands). Small proportions of kenophytes are characteristic of mountain regions, large proportions are in the flatland areas of the steppe and forest-steppe regions of Ukraine. Comparison with older data plots sampled in 1950-1989 let us make a conclusion that the proportion of kenophytes increased at least in one habitat type (oak-hornbeam woods).